Modernization and Tradition: Kutai Kartanegara Government's Legal Policy in Maintaining the Existence of Erau Culture in the Era of Revolution 4.0 - Taufiq, Muhammad; Tri Sukma, Ayu Mega; Suparno, Achmad Suparno; Yulianingrum, Aullia Vivi (Al-Adalah: Jurnal Hukum dan Politik Islam, 2025)
In the Industrial Revolution 4.0 era, technological advancements present challenges and opportunities for preserving local wisdom. This study examines the sustainability of the Erau tradition in Kutai Kartanegara, which faces pressures from modernization. Using a normative legal approach and library research methods, this research explores the intersection of law, local wisdom, and digital transformation in cultural preservation. The findings highlight that while modernization may threaten cultural authenticity, strategic digitalization and legal protection can safeguard traditions from excessive commercialization. Government regulations, including regional policies on cultural preservation, play a crucial role in balancing industrial development with cultural sustainability. Furthermore, public awareness and active community engagement are essential in integrating traditional values with contemporary technological frameworks. By emphasizing the role of legal frameworks and digital innovation, this study provides strategic insights for policymakers in fostering a sustainable cultural heritage amidst globalization.